The Moderating Role of Bank Size in Intellectual Capital, Leverage, and Financial Performance: Indonesian Islamic Commercial Banks 2019–2023 - Dhidhin Noer Ady Rahmanto; Ardila Septi Priwanda (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This study examines the effects of intellectual capital efficiency and leverage on the financial performance of Indonesian Islamic commercial banks, with bank size as a moderating variable. It addresses inconsistent prior findings by testing whether bank scale explains differences in the performance effects of intangible resources and financial structure. Research Methods: Using balanced panel data from nine Islamic commercial banks during 2019–2023, this study analyzes 45 bank-year observations. Financial performance is proxied by lnROA, intellectual capital by VAIC, leverage by DER, and bank size by ln(total assets). The data are analyzed using panel-based moderated regression. Results: The Random Effect Model shows that VAIC positively affects financial performance (β = 0.5449; p < 0.001), while DER has no significant direct effect (β = -0.0418; p = 0.5927). Bank size does not moderate the VAIC-performance relationship (β = 0.1626; p = 0.2663), but negatively moderates the DER-performance relationship (β = -0.2780; p < 0.001). Conclusion: The study contributes by applying panel-based moderation analysis to Islamic bank performance. Islamic banks should strengthen intellectual capital and manage leverage prudently as bank scale increases.